STATE REGULATION OF INNOVATIVE ACTIVITIES IN UZBEKISTAN IN THE CONTEXT OF ECONOMIC MODERNIZATION (Multidisciplinary Journal of Science and Technology, 2024)
This article provides an overview of the state regulation of innovative activities in the context of the modernization of the economy in Uzbekistan. The government of Uzbekistan has recognized the importance of innovation in diversifying the economy and competing globally. Through strategic policy and regulatory initiatives, Uzbekistan aims to create a favorable environment for innovation and technological progress. The Ministry of Innovative Development (MID) plays a crucial role in formulating strategies, supporting research and development, and coordinating with other state bodies.